2022
DOI: 10.4102/phcfm.v14i1.2911
|View full text |Cite
|
Sign up to set email alerts
|

Challenges experienced by community health workers and their motivation to attend a self-management programme

Abstract: Background: Community health workers (CHWs) are change agents expected to assist in decreasing the global burden of disease in the communities they serve. However, they themselves have health risk behaviours, which predispose them to non-communicable diseases and thus need to be empowered to make better health choices. There is a gap in literature detailing the challenges faced by CHWs in addressing their own health risk behaviours.Aim: This study aimed to explore the challenges experienced by CHWs in carrying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
(64 reference statements)
1
19
0
Order By: Relevance
“…Among the rural communities in the developing nations, prompt response to minor ailments and referral to the appropriate health facilities when necessary, has been a great challenge among the local communities resulting to preventable death and high mortality rate in the rural communities. However, studies have shown that the presence of community health workers can reduce the situation and improve the overall public health of the rural dwellers [21,22]. In the present study, the community health workers appear to be complementing the overall objectives of the primary healthcare as well as the Sustainable Development Goal agenda.…”
Section: 392 Acceptedmentioning
confidence: 50%
See 1 more Smart Citation
“…Among the rural communities in the developing nations, prompt response to minor ailments and referral to the appropriate health facilities when necessary, has been a great challenge among the local communities resulting to preventable death and high mortality rate in the rural communities. However, studies have shown that the presence of community health workers can reduce the situation and improve the overall public health of the rural dwellers [21,22]. In the present study, the community health workers appear to be complementing the overall objectives of the primary healthcare as well as the Sustainable Development Goal agenda.…”
Section: 392 Acceptedmentioning
confidence: 50%
“…The health services must be accessible to all through Primary Health Care Centers in which basic medical help is available in every community, backed up by referral services for more specialized care. As a matter of fact, this is embedded in the goal of the National Health Policy, which is to bring about a comprehensive health care system based on PHC and backed up in the rural communities by community health workers, bringing a healthcare system that is promotive, protective, preventive, restorative and rehabilitative to all citizens within the available resources so that individuals and communities are assured of productivity, social well-being and enjoyment of living [11,12]. Unfortunately, this is yet to be achieved among many developing nations especially in the sub-Saharan Africa where the globally designated health goals are yet to be settled among the government and the population [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HSAs regularly have additional tasks added to their list of responsibilities without a corresponding increase in the workforce, consistent with what has been cited by several other studies on challenges faced by community health workforces. 17 COVID-19 provided an extreme example of this, as it added signi cantly to HSAs' workload without any task shifting of other responsibilities. Supervisors lamented the lack of fuel and motorbikes to conduct supervision visits, and others noted the need for more bicycles, as well as gumboots, umbrellas and raincoats for the rainy season.…”
Section: Hsa Professional Supportmentioning
confidence: 99%
“…The previous studies reported that many adolescents lacked information about their Sexual and Reproductive Health (SRH) and had wrong opinions about contraception (Andina, 2021). In addition, based on the regulation of the Minister of Health Number 8 of 2019 concerning Community Empowerment in the Health Sector which states, in the implementation of Community Empowerment in the Health Sector, it is necessary to involve cadres who act as mobilizers, extension workers and note takers (Johnson et al, 2022). The global shortage of health professionals has prompted an increase in the use of Community health workers (CHW) as a key cadre to meet public health needs (Barik et al, 2019).…”
Section: Evaluatingmentioning
confidence: 99%
“…The impact of child marriage is the death of girls aged 15-19 years as a result of pregnancy and childbirth at a young age, and babies born to mothers under 20 years are almost two times more likely to die during the first 28 days than babies born to mothers aged 20 -29 years (Chae & Ngo, 2017). In addition, married girls are more vulnerable to domestic violence (Johnson et al, 2022). Child marriage can increase the risk of pregnancy due to limited autonomy in the use of contraception.…”
Section: Introductionmentioning
confidence: 99%